1993
DOI: 10.1007/bf02348531
|View full text |Cite
|
Sign up to set email alerts
|

Water intake by the adult mayfly Epeorus ikanosis (Ephemeroptera: Heptageniidae) and its effect on their longevity

Abstract: Water drinking habits during flight in adult mayflies of Epeorus ikanonis Takahashi were observed and the effect of water intake on their longevity was examined. The study was carried out in a mountain stream in western Japan. Adult males collected a water droplet under the head capsule while alighting on the water surface and consumed it after moving to nearby riparian vegetation. The amount of water intake was experimentally estimated to be 9.7% of the bodyweight for males. Although females did not show the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…Despite these observations it does not, however, seem likely that there is active or frequent uptake of liquid by imagos of Cloeon, both because the surface of the mouth area is so water-repellent and because the stance of the imago, as in other may¯y species, makes it very dif®cult for the mouth to be brought into contact with the substratum or even with adjacent foliage. Takemon (1993) has, however, described imagos of Epeorus ikanonis alighting momentarily on the surface of a stream and picking up water droplets: but his conclusion, that because droplets disappear from the head region they must enter the gut, fails to take into account the alternative possibility that the droplets disperse as a thin ®lm over the outer surface of the imago, the process so frequently observed in the present study.…”
Section: Entry Of¯uids and Air Into The Gutcontrasting
confidence: 58%
“…Despite these observations it does not, however, seem likely that there is active or frequent uptake of liquid by imagos of Cloeon, both because the surface of the mouth area is so water-repellent and because the stance of the imago, as in other may¯y species, makes it very dif®cult for the mouth to be brought into contact with the substratum or even with adjacent foliage. Takemon (1993) has, however, described imagos of Epeorus ikanonis alighting momentarily on the surface of a stream and picking up water droplets: but his conclusion, that because droplets disappear from the head region they must enter the gut, fails to take into account the alternative possibility that the droplets disperse as a thin ®lm over the outer surface of the imago, the process so frequently observed in the present study.…”
Section: Entry Of¯uids and Air Into The Gutcontrasting
confidence: 58%
“…On the other hand, Flecker et al (1988) argued that swarming males of a heptageniid mayfly, Epeorus longimanus, are under strong intermale competition. This conclusion was supported by observation of relatively long adult life and multiple copulation by males in another heptageniid, Epeorus ikanonis (Takemon 1993).…”
Section: Introductionsupporting
confidence: 52%
“…A notable exception is a ground-copulating heptageniid mayfly, Epeorus ikanonis, for which female multiple copulation was confirmed. The females successively mated with different males in cages (Takemon 1993), and observation in the field confirmed that 12% of all females engaged in multiple copulation within a restricted period of 13 min before oviposition (Takemon 1990a).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is generally accepted that mayfly adults do not feed, although intake of water may occur ( Takemon 1993 ), and they usually live for a very short period of time. Mating, oviposition and, in some cases, dispersal are the main functions of this stage.…”
Section: Introductionmentioning
confidence: 99%